The New methodological strategy for online teaching-learning with "Digital Capsules". - Caterina Tiscornia; Lucia Santelices (Universidad de Murcia, 2023)
Introduction: In the recent pandemic scenario, achieving learning outcomes for institutions of higher education in health sciences has become a great challenge. The forced shift from face-to-face to distance learning has generated the need to adapt the existing traditional pedagogical designs. Objective: To describe an online teaching-learning methodological strategy that incorporates digital capsules and the level of satisfaction of students taking Basic Nutrition I of the Nutrition and Dietetics program during the year 2021. Methods: Cross-sectional study of descriptive scope circumscribed under a mixed methodological design. The sample was purposive. The methodological design of the didactic strategy was based on the model of Pozo C. et al, 2006, Hepp P, 2006 and Santelices L. et al, 2014. The digital capsules included digital animation. Descriptive statistics were used to analyze the results. Results: An online methodological strategy for working in health sciences careers with two learning spaces is described and the steps that could be taken to implement it are described. 94% of the students positively perceived its incorporation as a useful resource for their learning. Conclusions: The strategy works because students perceive that it facilitates their understanding, helps them retain information and apply it. However, it is necessary to review its structure because it does not favor the application of exercises involving mathematical procedures. The need arises to deepen experimental studies to gather more evidence.